Função endotelial como indicador prognóstico, influência nos níveis de atividade física em pessoas idosas e evidências científicas sobre a reabilitação pulmonar em pacientes com síndrome pós-COVID-19 - Oliveira, Murilo Rezende (2024)
The COVID-19 pandemic has brought significant challenges to public health, particularly for vulnerable populations such as older people, COVID-19 patients, and those with persistent symptoms post-infection (Post-COVID-19 Syndrome). Given the knowledge gap and lack of evidence on the topic during the development of this thesis (from 2020 to 2024), our research group conducted studies to elucidate the main issues at each stage following the onset of COVID-19. Below are three of these studies: Study I - Objective: To evaluate the relationship between flow-mediated dilation (FMD) of the brachial artery, a non-invasive measure of endothelial function, with hospitalization days and mortality in patients diagnosed with COVID-19, and to compare these measures and outcomes in patients with and without COVID-19. Methods: A prospective observational study was conducted with 180 participants, including both confirmed COVID-19 patients (COVID-19 group) and suspected COVID-19 patients (Non-COVID-19 group). Clinical assessment and FMD measurements were performed within the first 24-48 hours of hospitalization. Patients were followed until discharge or death. Results: We evaluated 98 patients in the COVID-19 group and 82 in the Non-COVID-19 group. The COVID-19 group had longer hospital stays and higher mortality rates compared to the Non-COVID-19 group (p=0.01 and p<0.01, respectively). The COVID-19 group also showed a significantly greater reduction in both absolute and relative FMD (p<0.01 for both). Absolute FMD≤0.26 mm and relative FMD≤3.43% were identified as optimal cut-off points for predicting mortality and longer hospital stays. Kaplan-Meier analysis indicated that COVID-19 patients had a high probability of death within 10 days of hospitalization. Conclusion: Hospitalized COVID-19 patients exhibit early endothelial dysfunction, longer hospital stays, and higher mortality compared to those hospitalized for other reasons. Study II - Objective: To evaluate the available evidence on the physical activity levels of older people during the COVID-19 pandemic. Methods: This systematic review, registered in PROSPERO (CRD42021241116), included cross-sectional and cohort studies. The New Castle-Ottawa Quality Assessment Scale was used to measure study quality. Results: A total of 25 studies were found, including 14 cross-sectional and 11 cohort studies. The studies indicated that the older population was highly affected regarding physical activity levels and lifestyle during the COVID-19-induced restrictions, quarantines, and lockdowns. There was a significant reduction in physical activity levels, leading to declines in physical fitness and an increase in sedentary behavior, factors directly related to increased frailty in this population. Conclusion: Physical activity levels in the older population decreased during the COVID-19 quarantine period worldwide. Strategies to maintain physical condition should be encouraged with exercises that meet the needs of the older people during the pandemic to maintain and improve their health. Study III - Objective: To establish the effects of pulmonary rehabilitation in patients with persistent symptoms post-COVID-19 infection. Additionally, to compare the modalities of pulmonary rehabilitation services (face-to-face and telerehabilitation) and the duration in weeks (4-8 weeks and >8 weeks). Methods: This systematic review, registered in PROSPERO (CRD42022310788), included randomized clinical trials. Data extraction and quality assessment were performed independently by two reviewers. Methodological quality was evaluated using the Cochrane Risk of Bias Tool (RoB-1). Results: The literature search retrieved 1,406 articles, of which 7 studies explored the effects of pulmonary rehabilitation in patients with post-COVID-19 syndrome. The meta-analysis showed an increase in exercise capacity with pulmonary rehabilitation compared to control (6-minute walk test: mean difference: 60.56 m, 95% confidence interval: 40.75−80.36), a reduction in fatigue (Fatigue Severity Scale: MD: -0.90, 95%CI: -1.49 to -0.31), but no change in dyspnea (MD: -0.57, 95%CI: -1.32 to 0.17) and muscle strength (MD: 3.03, 95%CI: -1.89 to 7.96). There were no differences between telerehabilitation and in-person pulmonary rehabilitation regarding effects on peripheral muscle strength (p=0.42), dyspnea (p=0.83), and fatigue (p=0.34). No differences were found between programs of 4-8 weeks and >8 weeks concerning exercise capacity (p=0.83), peripheral muscle strength (p=0.42), and dyspnea (p=0.76). Conclusions: Pulmonary rehabilitation improves exercise capacity and reduces fatigue in patients with post-COVID-19 syndrome. The duration of pulmonary rehabilitation (4-8 weeks vs. >8 weeks) or modality (telerehabilitation vs. face-to-face) did not affect the outcomes, but data were limited and based on subgroup analyses. More evidence is needed to determine the optimal delivery mode and duration of pulmonary rehabilitation for post-COVID-19 syndrome. Final Considerations and Future Directions: Based on the findings, we conclude that these results reinforce the importance of considering non-invasive endothelial function assessment using FMD early in hospitals for COVID-19 patients. Additionally, this study underscores the need to seek measures to improve and restore physical activity levels in the elderly in the post-pandemic period and highlights the essential role of pulmonary rehabilitation in patients who were infected with COVID-19. However, evidence on the best form of distribution and duration of rehabilitation remains insufficient, and high-quality clinical trials are needed.